The dialectic of the Ecological ICMS in Londrina: aesthetic and ecosystemic function of landscape elements in municipal conservation units - Santos, Sheila Castro dos; Dias, Maico Eduardo Dias; Brandão , Alessandro Rodrigues de Lima; Lima, João Pedro Coelho de; Silva , Giovana Maria Galhardo (Technical and Scientific Journal Green Cities, 2025)
Objective - To analyse and highlight the maintenance of Conservation Units in the municipality of Londrina, using ICMS-Ecológico resources, the implementation of the Cidades +Verdes programme in 2024 and SDG 11 as a basis.Methodology - The research used a qualitative-quantitative approach and involved making historical series maps covering the period from 2009 to 2025.Originality/Relevance - The research demonstrates the relevance of the ICMS-Ecológico as an effective tool for incentivising the maintenance of green areas in cities, in line with the perspective of SDG 11, which focuses on making cities more resilient and sustainable. The study is original in that it analyses the application of this financial mechanism in conjunction with local initiatives.Results - It was observed that the ICMS-Ecológico, implemented in the state of Paraná, is a very relevant tool for maintaining green areas. The intensification of building and soil sealing in cities makes it increasingly necessary to have areas with trees, which facilitate the percolation of rainwater. Providing resources for the conservation and implementation of these areas is becoming a public environmental policy.Theoretical/Methodological Contributions - The study contributes theoretically by highlighting the effectiveness of fiscal mechanisms such as the ICMS-Ecológico in promoting environmental public policies at municipal level, and methodologically by using historical series analysis through maps to monitor the evolution of Conservation Units.Social and Environmental Contributions - Conservation Units are essential for the urban population, as they promote ecological interactions and offer a space to connect with local biodiversity. This provides a momentary ‘breather’ from the pressures of everyday life, improving quality of life. Maintaining green areas is fundamental to mitigating the effects of soil sealing, facilitating the percolation of rainwater. In addition, the conservation of these areas contributes to preserving the remnants of biodiversity, fauna and flora in Brazilian cities and municipalities.
Keywords: Ecological interaction; Public funding; Resilience